Stewardship and social justice: implications of using the precautionary principle to justify burdensome antimicrobial stewardship measures - Johnson, T (Springer, 2024)
Antimicrobial resistance has been termed a ‘silent pandemic’, a ‘hidden killer.’ This language might indicate a threat of significant future harm to humans, animals, and the environment from resistant microbes. If that harm is uncertain but serious, the precautionary principle might apply to the issue, and might require taking ‘precautionary measures’ to avert the threat of antimicrobial resistance, including stewardship interventions like antibiotic prescription caps, bans on certain uses in farming sectors, and eliminating over-the-counter uses of antibiotics. The precautionary principle is a useful tool in ethical analyses of antimicrobial stewardship measures, but as I argue in this article, it ought not be used as a standalone tool. The principle considers the magnitude of harms to be averted and those arising from precautionary measures, but—importantly—it does not consider the distribution of those harms. That may raise issues of social justice if the harms of stewardship measures befall already disadvantaged populations. To avoid this blind spot in ethical analysis using the precautionary principle, it ought never be used alone, but rather always alongside justice-considering ethical concepts such as reciprocity, benefit-sharing, or a just transition.